Experimental Investigation on the Failure Behavior of Carbon Fiber Reinforced Polymer (CFRP) Strengthened Reinforced Concrete T-beams - Junaedi Utomo; Muhammad Nur Khusyeni; Windu Partono; Ay Lie Han; Buntara S. Gan (Civil Engineering Dimension, 2021)
Carbon Fiber Reinforced Polymers (CFRP) are widely used as external concrete reinforcement. The behavior of T-beams strengthened in shear and flexure using CFRP sheets and plates was studied to analyze the load carrying capacity and failure mode as compared to conventional concrete members. The bonding response of the plate-to-concrete was investigated by comparing a specimen with a plate anchored at the far ends, one without anchoring. The sheets were in situ wet lay-up, the plate was pre-impregnated and pultruded during manufacturing. The test result suggested that this integrated strengthening method notably improved the load-carrying capacity, it was also demonstrated that anchoring had a positive but insignificant effect on the moment capacity and deformation. The influence of anchoring was noteworthy from the point of view that it shifted the failure mode from debonding to CFRP plate rupture. The most important factors influencing the behavior of CFRP strengthened beams are outlined.